Teacher Training - Lee Hsia Carmel Heah (Journal of Modern Languages)
This study reveals that various consultant to the Project have pointed out that UMSEP courses demand more of the teacher than other courses. The study mentions that UMSEP sees the teacher as the 'mediator' between the materials and the student and allows the teacher as a certain amount of discretion especially with regard to procedures, to adapt them when necessary to ensure that the learning objectives of the course are attained in the most efficient and economical way possible in terms or time taken, effort, anxiety, etc. The paper also states that there are different teaching styles. Therefore, the guiding principle in training is to help teachers perceive options available, extend their repertoire or skill and, by familiarizing them with the principles under the courses, improve their ability to select appropriately from these skill options.